2012
DOI: 10.1002/adma.201202805
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Calculations of Lithium‐Ion Migration at a Coherent Grain Boundary in a Cathode Material, LiCoO2

Abstract: Results of theoretical calculations are reported, examining the effect of a coherent twin boundary on the electrical properties of LiCoO(2) . This study suggests that internal interfaces in LiCoO(2) strongly affect the battery voltage, battery capacity, and power density of this material, which is of particular concern if it is used in all-solid-state Li-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
148
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 19 publications
12
148
1
Order By: Relevance
“…15,25 Because the equation is an exponential function of E m with a 2 ν as a pre-exponential factor, E m is generally more important than a and ν.…”
Section: Ionic Conduction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…15,25 Because the equation is an exponential function of E m with a 2 ν as a pre-exponential factor, E m is generally more important than a and ν.…”
Section: Ionic Conduction Mechanismmentioning
confidence: 99%
“…First-principles calculation is a powerful tool for analyzing defect formation and conduction mechanisms. [1][2][3][4][5][6][7][8][9][10][11] Although first-principles calculations with the nudged elastic band method (NEBM) can reveal a trajectory and an activation energy between two particular states, [12][13][14][15] the whole conduction path must be assumed before the calculations. First-principles molecular dynamics (FPMD) simulates atomic behaviors in complex crystals at finite temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles calculations have shown that there is three orders of magnitude increase of the diffusion constant for Li migration along TBs than that across TBs in LiCoO 2 . [91] An in situ STEM study of a single SnO 2 nanowire with TBs confirmed that Li ions preferentially intercalated near the (101) TB, which acted as a conduit for Li-ion diffusion in the nanowire. As shown in Figure 7, the lithiated SnO 2 nanowire exhibits darker-contrast stripes along the TB and in the [001] direction than the pristine nanowire exhibits; these stripes indicate Li-ion intercalation.…”
Section: Two-step Conversion Processmentioning
confidence: 99%
“…The cathode material is a key component to determine the capacity, cyclability and power/energy density of LIBs. However, conventional cathode materials, such as LiCoO 2 , LiMn 2 O 4 , LiFePO 4 and LiNi 1/3 Co 1/3 Mn 1/3 O 2 , all deliver low discharge capacity far below 200 mAh g À1 , indicating that alternative positive electrode materials with higher energy density than conventional cathode materials are required to meet the design needs of future rechargeable batteries [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%